Analisis Faktor-Faktor Penghambat Penyelesaian Skripsi Mahasiswa UIN Raden Mas Said Surakarta - Afifah Khoirunnisa; Devi Putri Rahmawati Permatasari; Izzatun Nisa; Miladiya Ulfa Nahdiyana; Muhamad Misbakhul Munir; Ulum Arofatul Jannah (Academica: Journal of Multidisciplinary Studies, 2022)
Writing a thesis is one of the problems in completing student studies.  Based on the results of observations, there are still many students of UIN Raden Mas Said who have not completed their thesis on time.  This research is a descriptive qualitative research that aims to describe the inhibiting factors in the completion of the thesis.  The subjects in this study were students of UIN Raden Mas Said who had not graduated with a study period of more than four years.  The results showed that there were 9 factors that hindered the completion of the script.  Of the 9 factors, researchers grouped into 2 factors, namely internal factors and external factors.  Internal factors in the form of physical and mental health and academic ability.  While external factors in the form of lecturer guidance and references, the environment of friends and family and other activities. Keywords: internal factor; external factor; finishing the thesis undergraduate